The case for UF/MF pretreatment to RO in seawater applications - Pearce, G.K. (Desalination, 2007)
UF has gradually gained acceptance as the preferred pre-treatment to RO, with a steadily increasing list of references from UF/MF suppliers, in a range of seawater, brackish water, and wastewater applications. However, although perceived as desirable, UF/MF is also thought to be an expensive option, and consideration of UF/MF is sometimes restricted to applications which are thought to be especially problematic. In wastewater treatment applications, UF/MF is the pretreatment technology of choice due to the highly fouling nature of the feed. Also, brackish water feeds also often utilize UF/MF pretreatment, since the higher RO fluxes which can be employed as a consequence of improved pretreatment give a clear advantage to the overall system cost. However, the case for UF/MF pretreatment in seawater applications is less clear cut. For beach well sources, conventional pretreatment, probably only consisting of cartridges, is sufficient, and there would be little advantage in using UF/MF. Surface water sources, which make up the majority of seawater duties, would benefit from UF/MF in terms of technical performance, but the economic case is often a close decision. This paper considers the factors which favour UF/MF pretreatment for seawater applications, employing an open intake. The performance advantage of UF/MF, and the resulting improvement in RO costs, will be weighed against the additional capex costs of pretreatment. The advantages of UF/MF are examined for a case study for an Eastern Mediterranean feed. In the Study, it is shown that the additional cost of UF/MF is paid for simply by the savings on chemicals and consumables. The additional cost of UF in terms of capex and membrane replacement is 2.9 cents/m 3. However, UF reduces RO replacement, saving 1.2 cents/m 3, and reduces chemical cost for both dosing, and RO cleaning. If the RO cleans are reduced from three cleans/y to two cleans/y, the saving amounts to 1.7 cents/m 3, which with the RO replacement saving pays for the UF/MF. If two cleans are saved, UF/MF becomes cheaper than conventional pre-treatment by 0.7 cents/m 3. This ignores other potential benefits arising from the 33% space saving of UF/MF, and the opportunity to increase RO flux and recovery. These factors will be the subject of a follow up paper.